Manganese dioxide nanowire-based bio-based porous carbon electrode material and preparation method and application thereof
By using bio-based porous carbon carriers in the positive electrode material of lithium sulfur battery and preparing manganese dioxide nanowires by hydrothermal method, the problems of low sulfur utilization and shuttle effect in lithium sulfur batteries are solved, and higher primary discharge capacity and lower capacity attenuation rate are achieved.
Patent Information
- Application Number
- CN202510022734.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-25
AI Technical Summary
Lithium sulfur batteries have problems with insufficient insulation characteristics and utilization rate of sulfur, as well as shuttle effects caused by the intermediate product polysulfide.
Manganese dioxide nanowires were prepared by one-step hydrothermal method using bio-based porous carbon as the carbon substrate, and loaded them on porous carbon to form a honeycomb-like porous structure to enhance the chemical adsorption of manganese dioxide and polysulfides.
It significantly improves the specific capacity and cycle stability of the primary discharge of lithium-sulfur batteries, reduces the capacity attenuation rate, and improves the electrochemical performance.
Smart Images

Figure CN119890263A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of positive electrode materials for lithium-sulfur batteries, and in particular to a bio-based porous carbon electrode material based on manganese dioxide nanowires, and a preparation method and application thereof. Background Art
[0002] Lithium-sulfur batteries have an ultra-high theoretical capacity of 1675 mA·h / g and are a very important type of lithium battery. However, lithium-sulfur batteries have problems with the insulating properties and insufficient utilization of sulfur, as well as the shuttle effect caused by the intermediate product polysulfide.
[0003] Carbon materials are currently the most common sulfur carriers. Due to their high specific area and high conductivity, they ensure high sulfur loading and promote the transmission of electrons / ions. For example, the existing document 1 (a porous carbon material based on discarded monk fruit core and its preparation method and application, patent publication number: CN117886317A) The previous research results of the inventor of the present invention use discarded monk fruit core as a carbon source. When used for the positive electrode of a lithium-sulfur battery, the initial discharge specific capacity is 1310mAh / g at a current density of 0.1C. However, subsequent studies have found that this technical solution cannot effectively capture and catalyze the conversion of lithium polysulfides (LiPSs) during the cycle because there is only a weak physical interaction between polysulfides and non-polar carbon, which inevitably causes a shuttle effect, resulting in a high capacity attenuation rate. In order to solve the above problems, polar metal oxides can be compounded with carbon to establish a strong chemical interaction between polar metal oxides and polysulfides, thereby effectively reducing polysulfide shuttling and improving the cyclability of the battery. Among them, MnO 2 It has the advantages of high theoretical specific capacitance, low cost and environmental protection, which can solve the above problems. MnO prepared by conventional methods 2 There are problems of poor conductivity and small active area, which leads to the 2 The specific capacity is low when used as the positive electrode of lithium-sulfur batteries.
[0004] MnO 2 Combined with carbon materials, it can solve the problem of non-polar carbon materials and MnO 2 The problems of each of them are solved at the same time, that is, the problems of shuttle effect, poor conductivity and small active area are solved at the same time. For example, the existing literature 2 (Shao-Zhuan H, YiCai, Jun Jin, et al. Unique walnut-shaped porous MnO 2 / C nanospheres with enhanced reaction kinetics for lithium storage with high capacity and superior rate capability.J.Mater.Chem.A, 2016, 4, 4264-4272), with KMnO 4 and NH 4 HCO 3 As raw material, PVP was used as auxiliary surfactant to prepare MnO 2 Nanosphere particles are loaded on carbon and when used in lithium-ion batteries, the capacity can reach 1176 mAh / g at a current of 100 mA / g. 2 Combined with carbon materials, however, the resulting MnO 2 The microstructure of the nanosphere is nano-spherical structure, and the particle diameter is 100nm, resulting in nano-spherical MnO 2 The shuttling of polysulfides cannot be effectively restricted, that is, the shuttling effect cannot be inhibited.
[0005] In addition, in other technical fields, for example, when manganese dioxide and carbon materials are composited and applied to supercapacitor materials, the existing document 3 (Zhang, W, Yuan, X, Yan, X et al. Tripotassium citrate monohydrate derived carbon nanosheets as a competent assistant to manganese dioxide with remarkable performance in the supercapacitor. Front. Chem. Sci. Eng. 16, 420–432 (2022).) grows manganese dioxide nanosheets on the surface of carbon nanosheets derived from tripotassium citrate monohydrate and applies them to supercapacitors. After 10,000 charge and discharge cycles, 75.3% of the initial capacitance is retained, that is, basically good cycle stability. Since this technical solution needs to apply the composite material to the field of supercapacitors, both manganese dioxide and carbon materials are prepared into nanosheet structures to obtain the performance of double-layer capacitors. However, the nanosheet structure is not suitable for the field of lithium-sulfur batteries. The reason is that the specific surface area of manganese dioxide in the nanosheet structure is small and it cannot adsorb enough polysulfides, thereby inhibiting the shuttle effect.
[0006] For example, in the field of hydrogen storage material catalysts, the previous work results of the research group of the inventor of the present invention, the existing document 4 (a bimetallic MnTi-MOF derivative MnTi@C material based on regulating the crystal structure and its preparation method and application; patent publication number: CN118002113A.) prepared a MnTi@C material with a hexagonal pyramid structure by a solvothermal method, and obtained a technical effect of a hydrogen release amount of 5.3wt% under the conditions of a hydrogen release temperature of 300°C and a hydrogen release time of 180s, and had good isothermal hydrogen release kinetics. Similar to the existing document 3, this technical solution needs to apply the composite material to the catalyst field, so the microscopic morphology is adjusted to a hexagonal pyramid structure, but the hexagonal pyramid structure is not suitable for the field of lithium-sulfur batteries, because the hexagonal pyramid structure cannot provide more active sites and cannot effectively inhibit the shuttle effect.
[0007] However, it is known from Existing Documents 2, 3 and 4 that manganese dioxide needs to be adjusted to have different microscopic morphologies depending on the technical field in which it is applied. Summary of the invention
[0008] The purpose of the present invention is to provide a bio-based porous carbon electrode material based on manganese dioxide nanowires and a preparation method and application thereof.
[0009] The present invention aims at solving the technical problems existing in the prior art, and uses bio-based porous carbon as a carbon substrate to prepare manganese dioxide nanowires by a simple one-step hydrothermal method, so as to change the single physical adsorption to a stronger chemical adsorption of polysulfide. Specifically, the present invention involves the following principles:
[0010] 1. Use bio-based porous carbon, which has multiple functional groups and high specific surface area, as a carbon substrate with large specific surface area;
[0011] 2. Preparing manganese dioxide with a nanowire structure by adjusting the molar ratio of manganese sulfate and potassium permanganate, and loading the manganese dioxide with the nanowire structure on porous carbon;
[0012] 3. Through a simple one-step hydrothermal method, manganese dioxide with a nanowire structure is prepared and the manganese dioxide nanowires are composited with bio-based porous carbon materials.
[0013] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0014] A bio-based porous carbon electrode material based on manganese dioxide nanowires is prepared by a one-step hydrothermal method using manganese sulfate, potassium permanganate and bio-based porous carbon as raw materials to obtain a bio-based porous carbon electrode material based on manganese dioxide nanowires, referred to as C-MnO 2 -NW; the C-MnO 2-NW's basic microstructure remains a honeycomb porous structure, and the surface of the honeycomb porous structure is loaded with manganese dioxide nanowires of nanowire structure, with an average diameter of 40-60nm and a specific surface area of 1650-1800m 2 / g.
[0015] A method for preparing a bio-based porous carbon electrode material based on manganese dioxide nanowires comprises the following steps: first, using MnSO 4 、KMnO 4 and bio-based porous carbon GC meet a certain amount of substance ratio. Under certain conditions, MnSO 4 、KMnO 4 and GC are placed in deionized water and stirred to obtain a reaction solution, and then, under certain conditions, the reaction solution is subjected to a hydrothermal reaction by a one-step hydrothermal method, and finally, the product obtained by the hydrothermal reaction is dried under certain conditions to obtain a bio-based porous carbon electrode material C-MnO based on manganese dioxide nanowires. 2 -NW;
[0016] In the preparation method, MnSO 4 、KMnO 4 The molar ratio of GC is 3:5:6;
[0017] In the preparation method, the conditions for stirring and mixing the reaction solution are: the stirring temperature is room temperature, and the stirring time is 1-6h;
[0018] In the preparation method, the conditions of the hydrothermal reaction are: the hydrothermal temperature is 100-200° C., and the hydrothermal time is 1-6 h;
[0019] In the preparation method, the conditions for the drying reaction are as follows: the drying temperature is 80-150° C. and the drying time is 10-24 h.
[0020] The bio-based porous carbon electrode material based on manganese dioxide nanowires, when used as the positive electrode material of lithium-sulfur batteries, has an initial discharge specific capacity of 1200-1300mAh / g at a current density of 0.2C; after 100 charge and discharge cycles, the discharge specific capacity is 1000-1200mAh / g, and the capacity attenuation rate is 10-15%.
[0021] The technical effect of the present invention can be known by the following tests:
[0022] The present invention has successfully prepared manganese dioxide through XRD testing; and, without adding KMnO 4 When , manganese dioxide cannot be synthesized;
[0023] The SEM test shows that C-MnO 2-The basic microscopic morphology of NW is maintained as a honeycomb porous structure, and a nanowire structure is loaded on the surface of the honeycomb porous structure, and the average diameter of the manganese dioxide nanowire is 40-60nm; and the raw material ratio significantly affects the microscopic morphology of manganese dioxide;
[0024] The present invention has been tested by BET and found that C-MnO 2 -NW has a specific surface area of 1650-1800m 2 / g; the specific surface area is affected by the microscopic morphology of manganese dioxide. When the microscopic morphology of manganese dioxide is nanowire, the specific surface area is the largest;
[0025] The present invention has been found that the C-MnO 2 -NW can provide an initial discharge specific capacity of 1200-1300mAh / g at a current density of 0.2C, and a remaining capacity of 1000-1200mAh / g after 100 charge and discharge cycles, with a capacity decay rate of 10-15%. The capacity decay rate is affected by the micromorphology of manganese dioxide. When the manganese dioxide is in the form of nanowires, the capacity decay rate is the lowest.
[0026] It can be seen from the above tests that the present invention has the following advantages over the prior art:
[0027] 1. The bio-based porous carbon used in the present invention has the characteristics of large initial specific surface area and more heteroatoms. Therefore, after further activation treatment, a higher specific surface area can be obtained, thereby improving the electrochemical performance;
[0028] 2. The present invention obtains manganese dioxide nanowires with a high active area by regulating the molar ratio of manganese sulfate and potassium permanganate, thereby significantly improving the chemical adsorption of polysulfides and further improving the electrochemical performance;
[0029] 3. The preparation process of the present invention is simple. Only a simple one-step hydrothermal method is required to prepare manganese dioxide with a nanowire structure and composite the manganese dioxide nanowires with the bio-based porous carbon material. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The C-MnO in Example 1 of the present invention 2 -XRD pattern of NW;
[0031] Figure 2 This is the SEM image of GC in Example 1 of the present invention;
[0032] Figure 3 The C-MnO in Example 1 of the present invention 2 -SEM image of NW;
[0033] Figure 4This is a constant current charge-discharge cycle diagram of GC at a current density of 0.2C in Example 1 of the present invention;
[0034] Figure 5 The C-MnO in Example 1 of the present invention 2 -NW constant current charge-discharge cycle diagram at 0.2C current density;
[0035] Figure 6 is the XRD pattern of C in Comparative Example 1 of the present invention;
[0036] Figure 7 MnO in Comparative Example 2 of the present invention 2 -SEM image of NW;
[0037] Figure 8 MnO in Comparative Example 3 of the present invention 2 -SEM image of NS;
[0038] Fig. 9 MnO in Comparative Example 4 of the present invention 2 -SEM image of NR;
[0039] Fig.10 The C-MnO in Comparative Example 5 of the present invention 2 -Constant current charge-discharge cycle diagram of NS at 0.2C current density;
[0040] Fig.11 The C-MnO in Comparative Example 6 of the present invention 2 -NR constant current charge and discharge cycle diagram at 0.2C current density;
[0041] Fig.12 The C-MnO in Comparative Example 7 of the present invention 2 -SEM image of NW-2;
[0042] Fig.13 The C-MnO in Comparative Example 8 of the present invention 2 -SEM image of NW-3;
[0043] Fig.14 The C-MnO in Comparative Example 9 of the present invention 2 -SEM image of NW-5. DETAILED DESCRIPTION
[0044] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0045] Example 1
[0046] A method for preparing a bio-based porous carbon electrode material based on manganese dioxide nanowires comprises the following steps: first, using MnSO4 、KMnO 4 The molar ratio of MnSO to bio-based porous carbon GC was 3:5:6. Under the conditions of room temperature and 2h stirring, MnSO 4 、KMnO 4 and GC were placed in deionized water and stirred to obtain a reaction solution. Then, the reaction solution was subjected to a hydrothermal reaction by a one-step hydrothermal method at a hydrothermal temperature of 175°C and a hydrothermal time of 4 hours. Finally, the product obtained by the hydrothermal reaction was dried at a drying temperature of 100°C and a drying time of 12 hours to obtain a bio-based porous carbon electrode material based on manganese dioxide nanowires, referred to as C-MnO 2 -NW.
[0047] In order to prove that C-MnO 2 -NW composition, and XRD test was performed. The test results are as follows Figure 1 As shown, C-MnO 2 -NW contains MnO 2 The test results show that MnO 2 Successfully loaded on GC.
[0048] In order to prove that C-MnO 2 -NW microstructure, SEM test was carried out. At the same time, for comparison, SEM test was carried out on the raw material GC.
[0049] The test results of GC are as follows Figure 2 As shown, the microstructure of GC is a honeycomb porous structure;
[0050] C-MnO 2 -NW test results are as follows Figure 3 As shown, C-MnO 2 -NW's basic microstructure remains as a honeycomb porous structure, and a nanowire structure is loaded on the surface of the honeycomb porous structure. The average diameter of the nanowire is 50nm. Combined with the XRD test results, it can be seen that the composition of the nanowire structure is MnO 2 .
[0051] To further prove that C-MnO 2 -NW microstructure, BET test was performed, and BET test was performed on the raw material GC at the same time.
[0052] The test results of GC are shown in Table 1. The specific surface area is 1501m 2 / g;
[0053] C-MnO 2 The test results of -NW are shown in Table 1. The specific surface area is 1705m 2 / g;
[0054] The test results show that loading manganese dioxide nanowires can increase the specific surface area by 13.6%.
[0055] Table 1 Comparison of specific surface areas of Example 1, Comparative Example 3 and Comparative Example 4
[0056] Specific surface area Example 1 1705 Comparative Example 3 1620 Comparative Example 4 1550 GC 1501
[0057] In order to prove that C-MnO 2 -NW is used as the technical effect of the positive electrode material of lithium-sulfur battery, and the lithium-sulfur battery is assembled for electrochemical performance testing. The method for assembling the lithium-sulfur battery is as follows: first, the sample to be tested is ball-milled with sulfur powder; the ball-milling conditions are as follows: under the atmospheric atmosphere, the mass ratio of the sample to be tested to sulfur powder is 3:7, the ball-to-material ratio is 100:5, the ball-milling speed is 250rpm, and the ball-milling time is 2h; after the ball-milling is completed, the carbon-sulfur composite material is obtained by the conventional melt diffusion method; then, the carbon-sulfur composite material is used as the active material, the conductive carbon black is used as the conductive agent, the polyvinylidene fluoride is used as the binder, and N-methylpyrrolidone is used as the solvent, and the active material, the conductive agent, and the binder are prepared in a mass ratio of 8:1:2; finally, the slurry is evenly coated on the aluminum foil to obtain the electrode sheet and the traditional lithium-sulfur battery electrolyte is added in the glove box to assemble the button battery. Since there is no need to distinguish, the obtained battery uses the abbreviation of the positive electrode material, that is, the lithium-sulfur battery obtained in the specific embodiment 1 is named C-MnO 2 -NW; at the same time, for comparison, the electrochemical performance of the raw material GC was tested.
[0058] The GC cycle charge and discharge test results are as follows: Figure 4 As shown, under the condition of current density of 0.2C, the initial discharge capacity is 808mAh / g; after 100 charge and discharge cycles, the discharge capacity is 665mAh / g, and the capacity decay rate is 21.5%;
[0059] C-MnO 2 -NW cycle charge and discharge test results are as follows Figure 5 As shown, under the condition of current density of 0.2C, the initial discharge capacity is 1230mAh / g; after 100 charge and discharge cycles, the discharge capacity is 1090mAh / g, and the capacity decay rate is 11.4%;
[0060] The test results show that loading manganese dioxide nanowires can significantly increase the specific capacity and reduce the capacity decay rate at the same time. The specific capacitance is increased by 52.2% and the capacity decay rate is reduced by 10.1%, which proves the role of manganese dioxide nanowires in the technical solution.
[0061] In order to prove that KMnO 4 The effect on the composite material, namely KMnO 4The role in the technical solution is to provide comparative example 1 without adding KMnO 4 Prepared composite materials.
[0062] Comparative Example 1
[0063] A kind of without adding KMnO 4 The preparation method of the composite material is the same as that of Example 1, except that KMnO is not added. 4 The composite material is obtained, referred to as C.
[0064] The XRD test results of C are as follows Figure 6 As shown in the figure, C only contains the diffraction peak of amorphous carbon, that is, there is no MnO 2 The test results show that manganese dioxide cannot be synthesized without adding potassium permanganate.
[0065] In order to prove the effect of GC, comparative example 2 is provided, in which manganese dioxide nanowires are prepared without adding GC; at the same time, in order to prove that in the preparation process, MnSO 4 and KMnO 4 The effect of the ratio of the amount of substances, referred to as the raw material ratio, on the microscopic morphology is provided. Comparative Examples 3 and 4 are provided, in which manganese dioxide is prepared with raw material ratios of 3:10 and 5:3 respectively.
[0066] Comparative Example 2
[0067] A manganese dioxide nanowire prepared without adding GC, the steps not specifically described are the same as those in Example 1, except that: manganese dioxide nanowires are obtained without adding GC, referred to as MnO 2 -NW.
[0068] MnO 2 -NW SEM test results are as follows Figure 7 As shown, MnO 2 -NW has a nanowire structure with an average diameter of 50 nm.
[0069] Compared with Example 1, it can be seen that the addition of GC has a significant effect on the 2 -NW microstructure has no obvious effect.
[0070] Comparative Example 3
[0071] A manganese dioxide nanosheet with a raw material ratio of 3:10, the steps not specifically described are the same as those in Comparative Example 2, except that: the MnSO 4 and KMnO 4 The molar ratio of 3:10 can produce manganese dioxide nanosheets, referred to as MnO 2 -NS.
[0072] MnO2 -NS SEM test results are as follows Figure 8 As shown, MnO 2 The microstructure of -NS is a nanosheet structure with an average diameter of 100 nm.
[0073] Compared with Comparative Example 1, it can be seen that increasing KMnO 4 The addition of potassium permanganate will cause the structure of manganese dioxide to change from a nanowire structure to a nanosheet structure. The reason is that when there is too much potassium permanganate, the reaction rate will be significantly increased, resulting in the formation of a large number of manganese dioxide nuclei in a short period of time. At the same time, due to the strong oxidizing property of potassium permanganate, further oxidation reaction will occur on the surface of the manganese dioxide nuclei generated in the initial stage of the reaction, thereby inhibiting the growth of the nuclei and affecting the growth direction of the nuclei, that is, causing manganese dioxide to grow in a specific direction and eventually forming a nanosheet structure.
[0074] Comparative Example 4
[0075] A manganese dioxide nanorod with a raw material ratio of 5:3, the steps not specifically described are the same as those in Comparative Example 2, except that: the MnSO 4 and KMnO 4 The molar ratio of 5:3 can obtain manganese dioxide nanorods, referred to as MnO 2 -NR.
[0076] MnO 2 -NR SEM test results are as follows Fig. 9 As shown, MnO 2 The microstructure of -NR is a nanorod structure with an average diameter of 200nm.
[0077] Compared with Comparative Example 1, it can be seen that the increase of MnO 2 The addition amount of manganese dioxide will cause the structure of manganese dioxide to change from a nanowire structure to a nanorod structure. The reason is that when manganese sulfate is relatively excessive, although it will also increase the reaction rate, resulting in the formation of a large number of manganese dioxide nuclei in a short time, manganese sulfate does not have strong oxidizing properties. Therefore, the growth rate of the manganese dioxide nuclei is significantly increased, and the growth direction grows uniformly in all directions, that is, a nanorod structure is finally formed.
[0078] It can be seen from Comparative Examples 2, 3 and 4 that the raw material ratio can significantly affect the microscopic morphology of manganese dioxide.
[0079] In order to further demonstrate the influence of the microscopic morphology of manganese dioxide on the electrode material, comparative examples 5 and 6 are provided, which are electrode materials prepared by loading manganese dioxide nanosheets and manganese dioxide nanorods on porous carbon, respectively.
[0080] Comparative Example 5
[0081] An electrode material based on manganese dioxide nanosheets, the steps not specifically described are the same as those in Example 1, except that: the MnSO 4 and KMnO 4 The molar ratio of the substance is 3:10, and the electrode material based on manganese dioxide nanosheets can be obtained, which is referred to as C-MnO 2 -NS.
[0082] C-MnO 2 The BET test results of -NS are shown in Table 1. The specific surface area is 1620m 2 / g;
[0083] Compared with GC, the increase in specific surface area of loaded nanosheets is only 7.9%;
[0084] Compared with Example 1, it can be seen that the nanowire structure has a larger specific surface area than the nanosheet structure, and the increase in specific surface area is 5.2%;
[0085] The test results show that the micromorphology can significantly affect the specific surface area.
[0086] C-MnO 2 -NS electrochemical performance test results are as follows Fig.10 As shown, under the condition of current density of 0.2C, the initial discharge specific capacity is 1120mAh / g; after 100 charge and discharge cycles, the discharge specific capacity is 938mAh / g, and the capacity decay rate is 16.3%.
[0087] Compared with GC, loading manganese dioxide nanosheets can simultaneously increase the specific capacity and reduce the capacity decay rate. The specific capacity is increased by 38.6% and the capacity decay rate is reduced by 5.2%.
[0088] Compared with Example 1, it can be seen that the nanowire structure has better effects on improving the specific capacity and capacity decay rate than the nanosheet structure;
[0089] Combining the results of SEM and BET tests, it can be seen that the direct cause affecting the electrochemical performance is the microscopic morphology of manganese dioxide, which proves the role of nanowires in the technical solution.
[0090] Comparative Example 6
[0091] An electrode material based on manganese dioxide nanorods, the steps not specifically described are the same as those in Example 1, except that: the MnSO 4 and KMnO 4 The molar ratio of the substance is 5:3, and the electrode material based on manganese dioxide nanorods can be obtained, which is referred to as C-MnO 2 -NR.
[0092] C-MnO 2 The BET test results of -NR are shown in Table 1. The specific surface area is 1550m 2 / g;
[0093] Compared with GC, the increase in specific surface area of loaded nanosheets is only 3.3%;
[0094] Compared with Example 1, it can be seen that the nanowire structure has a larger specific surface area than the nanorod structure, and the increase in specific surface area is 10.5%;
[0095] The conclusions obtained from the test results are consistent with those of Comparative Example 5, that is, the microscopic morphology can significantly affect the specific surface area.
[0096] C-MnO 2 -NR electrochemical performance test results are as follows Fig.11 As shown, under the condition of current density of 0.2C, the initial discharge specific capacity is 980mAh / g; after 100 charge and discharge cycles, the discharge specific capacity is 792mAh / g, and the capacity decay rate is 19.2%.
[0097] Compared with GC, it can be seen that although loading manganese dioxide nanorods can also increase specific capacity and reduce capacity decay rate at the same time, the increase in specific capacity is only 21.3%, and the reduction in capacity decay rate is only 2.3%;
[0098] Compared with Example 1, it can be seen that the nanowire structure has a significantly better effect of improving the specific capacity and capacity decay rate than the nanorod structure;
[0099] Combining the SEM test and BET test results, it can be seen that the conclusion obtained in Comparative Example 5 is also proved, that is, the direct cause affecting the electrochemical performance is the microscopic morphology of manganese dioxide, which further proves the role of nanowires in the technical solution.
[0100] It can be seen from Example 1, Comparative Example 5 and Comparative Example 6 that the raw material ratio can not only significantly affect the microscopic morphology of manganese dioxide, but also can further directly and significantly affect the specific capacity and capacity decay rate.
[0101] In order to further demonstrate the effect of the hydrothermal time on the composite material during the preparation process, comparative examples 7, 8 and 9 are provided, which are electrode materials prepared with hydrothermal times of 2 h, 3 h and 5 h, respectively.
[0102] Comparative Example 7
[0103] A bio-based porous carbon electrode material prepared by hydrothermal treatment for 2 h, wherein the steps not specifically described are the same as those in Example 1, except that the hydrothermal treatment time is 2 h, and the bio-based porous carbon electrode material is obtained, referred to as C-MnO 2 -NW-2.
[0104] C-MnO 2 -SEM test results of NW-2 are as follows Fig.12 As shown, only a small amount of manganese dioxide nanowires were loaded on the surface of the bio-based porous carbon.
[0105] Comparative Example 8
[0106] A bio-based porous carbon electrode material prepared by hydrothermal time of 3 h, the steps not specifically described are the same as those in Example 1, except that: the hydrothermal time is 3 h, and the bio-based porous carbon electrode material can be obtained, referred to as C-MnO 2 -NW-3.
[0107] C-MnO 2 -SEM test results of NW-3 are as follows Fig.13 As shown, only manganese dioxide nanowires were loaded on the surface of bio-based porous carbon;
[0108] It can be seen from Comparative Example 7, Comparative Example 8 and Example 1 that increasing the hydrothermal time can increase the loading amount of manganese dioxide nanowires.
[0109] Comparative Example 9
[0110] A bio-based porous carbon electrode material prepared by hydrothermal time of 5 h, the steps not specifically described are the same as those in Example 1, except that: the hydrothermal time is 5 h, and the bio-based porous carbon electrode material can be obtained, referred to as C-MnO 2 -NW-5.
[0111] C-MnO 2 -SEM test results of NW-5 are as follows Fig.14 As shown, although a large amount of manganese dioxide nanowires are loaded on the surface of bio-based porous carbon, the manganese dioxide nanowires are aggregated;
[0112] It can be seen from Comparative Example 9 and Example 1 that when the hydrothermal time is too long, although the loading amount of the manganese dioxide nanowires can be further increased, it also directly leads to the agglomeration of the manganese dioxide nanowires.
[0113] It can be seen from Example 1, Comparative Example 7, Comparative Example 8 and Comparative Example 9 that
[0114] When the hydrothermal time is short, the loading amount of MnO2 nanowires is small, which leads to the decrease of electrochemical performance;
[0115] When the hydrothermal time is too long, the loading amount of manganese dioxide nanowires is too much, which leads to agglomeration and the decline of electrochemical performance.
Claims
1. A bio-based porous carbon electrode material based on manganese dioxide nanowires, characterized in that: Using manganese sulfate, potassium permanganate and bio-based porous carbon as raw materials, a bio-based porous carbon electrode material based on manganese dioxide nanowires, abbreviated as C-MnO2-NW, can be obtained through a one-step hydrothermal method.
2. The bio-based porous carbon electrode material based on manganese dioxide nanowires according to claim 1, characterized in that: The basic microstructure of the C-MnO2-NW is maintained as a honeycomb porous structure, and the manganese dioxide nanowires with a nanowire structure are loaded on the surface of the honeycomb porous structure. The specific surface area of the C-MnO2-NW is 1650-1800m 2 / g.
3. The bio-based porous carbon electrode material based on manganese dioxide nanowires according to claim 2, characterized in that: The average diameter of the manganese dioxide nanowires is 40-60 nm.
4. A method for preparing a bio-based porous carbon electrode material based on manganese dioxide nanowires, characterized in that The following steps are involved: Firstly, with a certain amount of substance ratio among MnSO4, KMnO4 and bio-based porous carbon GC, under certain conditions, MnSO4, KMnO4 and GC are placed in deionized water and stirred to obtain a reaction solution. Then, under certain conditions, the reaction solution is subjected to a hydrothermal reaction by a one-step hydrothermal method. Finally, the product obtained by the hydrothermal reaction is dried under certain conditions to obtain a bio-based porous carbon electrode material C-MnO2-NW based on manganese dioxide nanowires.
5. The preparation method according to claim 4, characterized in that: In the preparation method, the molar ratio of MnSO4, KMnO4 and GC is 3:5:
6.
6. The preparation method according to claim 4, characterized in that: In the preparation method, the conditions for stirring and mixing the reaction solution are: the stirring temperature is room temperature, and the stirring time is 1-6h; In the preparation method, the conditions of the hydrothermal reaction are: the hydrothermal temperature is 100-200° C., and the hydrothermal time is 1-6 h; In the preparation method, the conditions for the drying reaction are as follows: the drying temperature is 80-150° C. and the drying time is 10-24 h.
7. The bio-based porous carbon electrode material based on manganese dioxide nanowires according to claim 1, characterized in that: When used as a positive electrode material for lithium-sulfur batteries, the initial discharge specific capacity is 1200-1300mAh / g at a current density of 0.2C.
8. The bio-based porous carbon electrode material based on manganese dioxide nanowires according to claim 1, characterized in that: When used as a positive electrode material for lithium-sulfur batteries, under the condition of a current density of 0.2C, after 100 charge and discharge cycles, the discharge specific capacity is 1000-1200mAh / g, and the capacity attenuation rate is 10-15%.
Citation Information
Patent Citations
Porous carbon material based on waste siraitia grosvenorii core as well as preparation method and application of porous carbon material
CN117886317A
Bimetal MnTi-MOF derivative MnTi-coated C material based on regulated crystal form structure and preparation method and application of bimetal MnTi-MOF derivative MnTi-coated C material
CN118002113A